Improvement plan in the administrative processes of customer services, document management and safety and health at work, in the SMEs of Palmira Valle del Cauca - lasso ojeda, Emilse yamilet
This research project is based on the importance that education developed by competencies has today and on solving real problems in the labor market. Due to the above, the Administrative Assistance Technician program within its curricular design determines that an apprentice must develop a highly competent technical and human according to the requirements that companies request to provide a service efficiently, effectively and timely with the application of processes and procedures that allow to dynamize the organizational administrative management. According to the above, the objective to be achieved is to design a plan to improve administrative processes for Medium Sized Enterprices - SMEs that help their growth and expansion of their labor market.